Studies on the thermal stabilization for Polyvinyl chloride by some metal stearates - A. Mahdi, Haider; Y. Kadhum, Mouayed; H. Anathiel, Amal (University of Thi-Qar Journal of Science, 2019)
In this study, preparation of some metal stearates derived from stearic acid with metals ; Iron , Cobalt, Nickel, Copper and Zinc . They were used as thermal stabilizers for Polyvinyl chloride. These metal stearates were identified by elemental analysis and infrared spectroscopy.I.R, spectroscopy within the rang 1500-1900 cm-1 was used to study the thermal stability for PVC containing prepared metal stearates , and that depending on thin films technique . The variations in the absorption bands intensity of the groups C = O , C = C , COO - at 195oC were studied at different times (15 ,30 ,45 , 60 min) from thermal stress. These variations resulted from the rule of the metal stearates in the stabilizing of polymer . U.V-V.S spectroscopy was used to study the thermal degradation of unstabilized PVC and the reprecipitated PVC from the stabilizers .This study was carried out by the investigation of the polymer resulted from the evolving of HCl from the polymer chain at 275nm and 385 nm corresponding to three and seven conjugated double bonds respectively .The results were indicated that metal stearates and their synergistic mixtures have the ability to stabilize PVC by decreasing the conjugated double bonds in the polymer . The thermal stability of the unstabilized PVC and PVC containing different metal stearates was investigation by thermogravimetric analysis (TGA). Many functions were calculated such as the decomposition temperature , rate of decomposition ,activation energy ,char content ,and percentage of HCl evolving from the polymer chain . The results indicated that metal stearates was increasing the thermal stability for PVC . TGA was also used to evaluate the synergistic effect for some mixtures of the prepared metal stearates (Zinc stearate with stearates of the Nickel ,Cobalt ,Copper , Iron ) , and it was found that these mixtures have high stabilizing ability for the PVC .